Pemikiran Hukum Islam Para Imam Mazhab (Ahlussunnah Wal Jama’ah) - Karunia, Khaerunnisa; Sultan, Loma; F, Fatmawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Law in Islam aims to regulate human interests to obtain benefits in life, so thinking in Islamic law continues to develop and goes hand in hand with the pace of development of the Muslim community itself. Laws in Islam certainly originate from the Al-Qur'an and Hadith so that everything is clearly explained and determined in these sources. The development of thought in Islamic law during the Tabi'in period experienced a golden age because there were many reforms in istinbath al-ahkam/making or enacting laws. This is the point of scientific progress in the Islamic world, especially in Islamic law.